The Just Noticeable Difference in Complexity of Jobs - Globerson, Shlomo (Management Science, 1977)
This paper investigates the magnitude of Nonrepetitive Time (NRT) change that will be subjectively perceived as significant. NRT is a previously developed index of job complexity and NRT change can be identified with the “Just Noticeable Difference” of job complexity. Together, they enable the job designer to evaluate the nature of the jobs and to compare the complexity of one job to another. The results indicate that two jobs would be subjectively considered to be significantly different one from the other in terms of their complexity, if the NRT index of one of them is larger by approximately 100 percent than the other.